Social Competence Main Aspects in Early Childhood Resilience in Risk Environments - Hamid Patilima (Universitas Panca Sakti Bekasi, 2024)
Children's social competency is one part of resilience that involves a child's capacity to engage, communicate, and adjust to their social environment. So interesting is competence that social media has piqued the curiosity of educators about children's early exposure to risky environments. The goal of this project is to develop children's resilience at a young age through social competence. Educators play a role in developing children's resilience in terms of social competence by fostering confidence, independence, self-control, and paying attention to others.